Mediating effect of lower extremity muscle strength on the relationship between mobility and cognitive function in Chinese older adults: A cross-sectional study - Chen, Yaoxin; Zhan, Yijun; Wang, Hong; Zhang, Hui; Cai, Yiwen; Wang, Liaoyao; Zhu, Wenyan; Shen, Haiyue; Pei, Jian (Frontiers in Aging Neuroscience, 2022)
Aging is a multifactorial process associated with irreversible decline in mobility and cognitive function. However, the mechanisms underlying the relationship between mobility and cognitive function remain elusive. In specific, the mediating effect of muscle strength, which is essential to maintain mobility, on this relationship has yet to be clarified. Accordingly, we performed a cross-sectional study involving Chinese older adults to understand the role of muscle strength in the relationship between mobility and cognitive function. The cognitive function and physical performance of 657 community-dwelling participants aged over 65 years old were observed. Cognitive function was assessed using the Mini-Mental State Examination, whereas physical performance, including mobility and muscle strength, was measured via Timed Up-and-Go Test and knee extension strength measurement. Data were statistically analyzed using PROCESS Model 4 developed by Hayes, and 595 complete data were finally included. Physical performance (mobility and muscle strength) was significantly correlated with cognitive function (p < 0.01). Muscle strength was negatively correlated with mobility (r = −0.273, p < 0.001) and positively correlated with cognitive function (r = 0.145, p < 0.001). Muscle strength accounted for 20.1% of the total mediating effects on the relationship between mobility and cognitive function, which revealed the key mediating role of lower extremity muscle strength in this relationship.